Identidad queer en la obra de Juan Pablo Sutherland. - Salomón Gebhard, José Luis (Nomadías, 2013)
This article discusses the essayistic texts of Nación Marica, book written by Juan Pablo Sutherland. It is intended, first, to describe queer identity from the theoretical perspective of the author, second, evaluate some of his narrative texts, especially the story "Furiosos en dos meses", included in the second edition of the stories book Angeles Negros. The theoretical analysis is based on the concept of performativity, questioning the difference between Sutherland's essay and literary discourse, making his text production a hybrid and continuum writing, defined as performative speech act. The analysis focuses on the referential condition of the pointed story, given some paratextual indications that the narrator includes in his act of enunciation.